2014
DOI: 10.1016/j.jmb.2014.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Technologies to Map the Protein Methylome

Abstract: Protein methylation plays an integral role in cellular signaling, most notably by modulating proteins bound at chromatin, and increasingly through regulation of non-histone proteins. One central challenge in understanding how methylation acts in signaling is identifying and measuring protein methylation. This includes locus-specific modification of histones, on individual non-histone proteins, and globally across the proteome. Protein methylation has traditionally been studied using candidate approaches such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 82 publications
1
66
0
Order By: Relevance
“…According to the accumulated evidences that lysine methylation is not histone-specific, lysine methyltransferases (KMTs) and lysine demethylases (KDMs) are now widely accepted. A recent massive proteomic analysis enabled mining of methylated proteins from whole cell extracts or enriched fractions (Carlson and Gozani, 2014;Chick et al, 2015;Wang et al, 2015). Only a few studies have been performed with regard to the relatedness of PTMs during brown adipocyte differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…According to the accumulated evidences that lysine methylation is not histone-specific, lysine methyltransferases (KMTs) and lysine demethylases (KDMs) are now widely accepted. A recent massive proteomic analysis enabled mining of methylated proteins from whole cell extracts or enriched fractions (Carlson and Gozani, 2014;Chick et al, 2015;Wang et al, 2015). Only a few studies have been performed with regard to the relatedness of PTMs during brown adipocyte differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few of these sites have been associated with specific KMTs, so a large number of enzyme/substrate relationships remain to be discovered (14). Techniques for linking KMTs to non-histone substrates are limited, and this remains a major challenge in understanding how lysine methylation participates in wider signaling processes (15). We recently reported a proteomic strategy to identify and measure lysine methylation by using the three malignant brain tumor domain repeats (3xMBT) of L3MBTL1 as a universal affinity reagent to capture modified proteins (10,16).…”
mentioning
confidence: 99%
“…Recent studies with nonplant material (e.g. mammalian cells and yeast [Saccharomyces cerevisiae]) using various novel enrichment techniques followed by MS/MS showed that high numbers of Arg (monomethylation and demethylation) and Lys (monodimethylation and trimethylation) are methylated (for an excellent overview on innovative methodologies, see Carlson and Gozani [2014]). These methylations are carried out by Arg or Lys methyltransferases (PRMTs and PKMTs, respectively) with S-adenosylmethionine (AdoMet) as methyl donor, thereby releasing S-adenosyl-homo-Cys (Biggar and Li, 2015) and coupling the cellular metabolic state to this PTM.…”
Section: Methylation Of Lys and Argmentioning
confidence: 99%